ANALISIS PERAN GURU DAN ORANG TUA DALAM PENDAMPINGAN INTERAKSI SOSIAL-EMOSIONAL ANAK ADHD DI MARINDAL - Maysarah; Heriyani; Marsyah Finkan Adtya; Wahda Khairunisya; Dwi Andini; Rahmadani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the role of teachers and parents in assisting the social-emotional interaction of a child with Attention Deficit Hyperactivity Disorder (ADHD) in Marindal. This research uses a qualitative descriptive approach with data obtained through interviews and observation. The subject of the study was a 9-year-old child with ADHD characteristics, such as high activity, difficulty controlling behavior, and difficulty socializing with peers. The results show that the child has good academic abilities, especially in reading, mathematics, contextual learning, memorization, iqro, drawing, and basic vocabulary in several foreign languages. However, the child still experiences obstacles in social interaction, such as difficulty playing with friends, feeling uncomfortable when touched, and sometimes pushing peers. The presence of a shadow teacher greatly helps the child follow classroom activities. Teachers provide individual learning assistance, especially in reading, because the child requires a focused and quiet environment. Parents also play an active role in supporting learning at home and maintaining communication with teachers. The collaboration between teachers and parents has created positive academic development, although the child’s social-emotional development still needs continuous assistance.